2018
DOI: 10.1097/pcc.0000000000001694
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Validation of the Vasoactive-Ventilation-Renal Score as a Predictor of Prolonged Mechanical Ventilation After Neonatal Cardiac Surgery*

Abstract: In this multicenter cohort of neonates who underwent cardiac surgery, the Vasoactive-Ventilation-Renal score was a reliable predictor of postoperative outcome and outperformed more traditional measures of disease complexity and severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
2
17
0
1
Order By: Relevance
“…In a limited number of prior studies, the VVR calculated at 48 hours (12,13) and at 12 hours [14,15] was found superior to admission and peak VVR measurements. We also found that admission measurement was performed poorly according to other measurement points.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In a limited number of prior studies, the VVR calculated at 48 hours (12,13) and at 12 hours [14,15] was found superior to admission and peak VVR measurements. We also found that admission measurement was performed poorly according to other measurement points.…”
Section: Discussionmentioning
confidence: 85%
“…In a recent multi-center study involving only newborns, like our study, score calculations were made in the postoperative 12-hour period, and the VVR score was found to be superior in determining prolonged MV duration (determined as > 96 hours in this study) compared to VIS, VI, and serum lactate. In this study, the cutoff value was expressed as 35 [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Several data-driven predictors of outcomes have also been developed and validated, such as the Vasoactive Inotropic Score (VIS) and Ventilation Index (VI), but are primarily utilized in research and have subjective variability. 3,4 A number of studies this year focused on utilizing current and novel biomarkers as predictors of adverse outcomes in patients undergoing congenital heart surgery.…”
Section: Predictors Of Outcomes In Congenital Cardiac Surgerymentioning
confidence: 99%
“…The vasoactive-ventilation-renal (VVR) score is a novel disease severity index which includes components reflecting cardiovascular, pulmonary, and renal function. Recently, the usefulness of the VVR score in pediatric patients undergoing cardiac surgery has been reported (2,3). In some studies (4,5), the VVR score was shown to be predictive in particular of a prolonged length of stay (PLOS) in the intensive care unit (ICU).…”
Section: Introductionmentioning
confidence: 99%